Molecular characterization of farmers' varieties of rice (Oryza sativa) - KUMAR, VIJAYA; KUMAR, SUSHIL; CHAKRABARTY, S K; MOHAPATRA, TRILOCHAN; DADLANI, MALAVIKA (The Indian Journal of Agricultural Sciences, 2015)
A study was carried out for characterization of 60 farmers' varieties using grain characters and 40 SSR (Simple Sequence Repeat) markers. Only a set of 8 (20%) primers were polymorphic yielding 16 bands (alleles) among these 60 varieties. The size of amplicons ranged from 120 bp (RM238) to 240 bp (RM551). The number of alleles per microsatellite ranged from 1 (RM238, RM119 and RM120) to 3 (RM259, RM234 and RM551) with an average of 2 alleles per locus. Major allele frequency ranged from 0.51 to 0.97 averaging 0.74. Genetic diversity ranged from 0.045 to 0.588 with a mean of 0.34. Considering the entire genotypic array, the mean value for polymorphism information content (PIC) for all microsatellites was 0.27. Microsatellite RM122 with 2 alleles had the maximum PIC value (0.37) and the microsatellite RM205 with 2 alleles had the minimum (0.27) value. The UPGMA cluster analysis grouped varieties into three main clusters with 58% genetic similarity and homing 24, 23 and 13 varieties, respectively. Grain characteristic- based clustering was better than molecular markers as accessions were in expected cluster. However, few accessions showed scattering to other sub-clusters. The diversity analysis revealed the distinct nature of farmers' varieties in a large number of clusters indicating greater diversity, which could be exploited in breeding programmes to combine grain traits and early vigor.